Stratigrafi Seismik untuk Interpretasi Fasies Pengendapan Berdasarkan Data Seismik 2D pada Daerah Lepas Pantai Onin, Palung Seram - FAUZI, Achmad ([Yogyakarta] : Universitas Gadjah Mada, 2013)
geology especially Onin offshore areas, Seram Trough is one of the target areas of hydrocarbon exploration in eastern Indonesia are generally only available seismic data. The seismic data can assist in the assessment of subsurface stratigraphic through the seismic stratigraphic approach. eismic S stratigraphic is interpretation of stratigraphy from seismic data (Vail & Mitchum, 1997 in Sukmono, 1999) in which there is discussion of seismic sequence and depositional facies. etermination of s D eismic sequence and depositional facies are the result of this study which are useful for studying hydrocarbon prospects. Sequences which can be identifiable are nine. Sequence one is equivalent with Bogal Limestone which is dominated by shelf/platform facies, sequence two is equivalent with Yefbie Shale which is dominated by delta plain facies, sequence three is equivalent with Demu Formation and Lelinta Shale which is dominated by delta front, sequence four is interpretated with Facet Group which is dominated by proximal basin and lower slope facies, sequence five is equivalent with Lower New Guinea Limestone which is dominated by shelf/platform facies, sequence six is equivalent with Upper New Guinea Limestone which is dominated by shelf/platform facies, sequence seven is equivalent transgression sequence which developed submarine canyon fill facies, sequence eight is equivalent progradasional sequence 1 which developed slope facies, sequence nine is equivalent progradasional sequence 2 which developed marine (slope) onlap. facies